Transcriptional modulation of inflammation, and aging in Indian obese adults following a 12-week yoga-based lifestyle intervention: A randomized controlled trial - Sharma, Piyush; Yadav, Raj Kumar; Khadgawat, Rajesh; Dada, Rima (Frontiers in Medicine, 2022)
Current evidence suggests obesity alters the expression of various genes related to oxidative stress, inflammation, and aging. The complementary therapy like yoga-based lifestyle intervention (YBLI) is used as an adjunct therapy to modern medicine. This study examines the efficacy of 12-weeks of YBLI with standard care (SC) on the expression of genes related to oxidative stress, inflammation, and aging in obese adults. This was a two-arm parallel randomized control trial implemented at Integral Health Clinic (IHC), an outpatient facility that regularly conducted YBLI programs for the prevention of lifestyle diseases like obesity and diabetes in the Department of Physiology, All India Institute of Medical Sciences (AIIMS), New Delhi. Blood samples at baseline and weeks 2,4 and 12 were collected from 72 adults (male n=21; female n=51) of age 20-45 years with a body–mass index (BMI) of 25–35 kg/m2 who were randomized to receive either a 12-week SC (n=36) or YBLI (n=36). SC included recommendations for the management of obesity as per Indian guidelines including a low-calorie individualized diet and physical activity. Asana (physical postures), pranayama (breathing exercises), and meditation were included in the YBLI. Primary outcomes were relative fold changes in the expression of genes associated with oxidative stress (Nuclear factor-kappa B [NF-Kappa B]), inflammation (Tumour necrosis factor-α [TNFα], interleukin-6 [IL-6]), and aging (human telomerase reverse transcriptase [TERT]) in peripheral blood mononuclear cells between the two groups at week-12. There were no significant changes in fold change of TERT, IL-6, and NF-kappa B between the groups at week 12. The relative fold change of TERT was significantly greater in the YBLI group (p=<0.0001) vs the SC group at 2 weeks. TERT expression was significantly increased at week 2 though the change was greater in the YBLI group (p<0.0001). TNF-α gene expression was significantly lower at weeks 2 and 4, compared to baseline level, in the SC group but it increased at week 12. The results while did not confirm our hypothesis, are important to share with the scientific society, to be able to improve prospective study designs and find optimal time/intervention/biological marker settings for this highly important scientific field.